Hypertension Patients' Knowledge, Attitudes, and Control Measures in Bukittinggi: A Qualitative Study - Apriza, Cici; Djuwita, Ratna; Martha, Evi; Besral, Besral (Jurnal Kesmas Jambi, 2025)
Hypertension remains a major global health concern, causing numerous deaths worldwide. Approximately 1.13 billion people suffer from hypertension, with an estimated 10.44 million deaths annually due to hypertension and its complications. This study aims to explore the knowledge, attitudes, and actions taken by hypertensive patients in Bukittinggi City. The research was conducted in the Mandiangin Health Center Working Area, involving 17 hypertension patients, one officer responsible for the Non-Communicable Diseases (NCD) program, and the head of the community health center. This qualitative study used a phenomenological approach, identifying three main themes: knowledge, attitude, and action. The sub-themes include "awareness of hypertension diagnosis," "emotional response to diagnosis," "hypertension management efforts," and "support from health workers." Findings indicate that most patients were unaware of their hypertension diagnosis until they experienced symptoms or were screened during routine checkups. The dominant hypertension management strategies involved seeking treatment at the community health center and maintaining dietary modifications. This study highlights the experiences of hypertensive patients in improving knowledge, attitudes, and behavioral strategies for better hypertension control.